2017
DOI: 10.1007/s12328-017-0762-z
|View full text |Cite
|
Sign up to set email alerts
|

Management of aorto-esophageal fistula secondary after thoracic endovascular aortic repair: a review of literature

Abstract: Aorto-esophageal fistula (AEF) is a rare and lethal entity, and the difficulty of making diagnosis of AEF is well-known. As promising results in the short-term effectiveness of thoracic endovascular aortic repair (TEVAR) promote its usage, the occurrence of AEF after TEVAR (post-TEVAR AEF) increases as one of the major complications. Therefore, we provide a review concerning the management strategy of post-TEVAR AEF. Although its representative symptom was reported as the triad of mid-thoracic pain and sentine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 73 publications
0
27
0
Order By: Relevance
“…Temporary measures, such as the insertion of the Sengstaken-Blakemore tube and embolization with isobutyl-2-cyanoacrylate, were used to stop the bleeding until surgery [9]. Endovascular techniques have shown favorable short-term outcomes [3,[10][11]. Thoracic endovascular aortic repair (TEVAR), proposed by Dake et al, had a success rate of 87% and a mortality rate of 19%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Temporary measures, such as the insertion of the Sengstaken-Blakemore tube and embolization with isobutyl-2-cyanoacrylate, were used to stop the bleeding until surgery [9]. Endovascular techniques have shown favorable short-term outcomes [3,[10][11]. Thoracic endovascular aortic repair (TEVAR), proposed by Dake et al, had a success rate of 87% and a mortality rate of 19%.…”
Section: Discussionmentioning
confidence: 99%
“…Still, there is also evidence suggesting that the conservative approach utilizing TEVAR alone is associated with fatal outcomes due to the risk of recurrent hemorrhage and sepsis. Therefore, current recommendations support the use of TEVAR as a bridge strategy, facilitating hemodynamic stabilization before the definite surgical procedure [3,14]. Primary repair of the esophageal defect could result in positive progression, particularly in small lesions detected early [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aortoesophageal fistula (AEF) usually results in fatal gastrointestinal bleeding and is associated with a high mortality rate, despite the use of advanced surgical and endovascular techniques [ 1 ]. Previous studies reported that nearly 60% of patients with AEF died within 6 months; the 1-year survival rate was only 28% [ 2 , 3 ]. Since the 1990s, thoracic endovascular aortic repair (TEVAR) has been increasingly used as a less invasive treatment for aortic aneurysm and aortic dissection [ 4 ]; however, post-TEVAR AEF has been frequently observed as a fatal complication [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since the 1990s, thoracic endovascular aortic repair (TEVAR) has been increasingly used as a less invasive treatment for aortic aneurysm and aortic dissection [ 4 ]; however, post-TEVAR AEF has been frequently observed as a fatal complication [ 5 ]. Due to the rarity of AEF, few studies have investigated its risk factors for mortality, or the long-term prognosis [ 2 ]. Therefore, we systematically reviewed the literature on AEF related to aortic lesions, including aortic aneurysm and dissection.…”
Section: Introductionmentioning
confidence: 99%